PRESCRIPTIVE MAINTENANCE ON THE FACTORY FLOOR: ANALYTICAL THEORETICAL REFLECTION - Barrozo de Souza, José; Santana Rocha, Sandra Mara (Revista Gestão da Produção Operações e Sistemas, 2024)
Purpose: Analyze the perceptions of researchers and experts in the implementation of Prescriptive Maintenance on the factory floor in companies located in Espírito Santo, Southeast Region of Brazil considering the strategies recommended by carrying out the SWOT analysis. Methodology/Approach: The methodological procedures used were a combination of three data collection mechanisms, a bibliographical research, considering the impacts of Prescriptive Maintenance on the factory floor and an empirical work, by sending a questionnaire to researchers and experts to analyze their perceptions. Furthermore, the application of the SWOT analysis (Strengths, Weaknesses, Opportunities and Threats) to evaluate the strategic considerations arising from said analysis. Findings: The study provides recommendations for managers and professionals working on the factory floor, showing the needs for improvement in maintenance tasks that is, considering the strategic impacts of Prescriptive Maintenance and the importance of digitizing the factory floor. Research, practical & social implications: The results of this study offer valuable perspectives for the formulation of strategic policies aimed at attracting the efficiency of physical assets. They also have important implications for Maintenance Management and can serve as a reference for future studies on the topic. Originality/ Value: Based on the data obtained, the authors present the importance of organizational synchronization between different sectors of companies considering the systemic view, therefore, recommending this model for small companies, due to the existence of barriers in the implementation of technological modernization in companies of this size using new methodologies of research.